PENGARUH BUDAYA KERJA TERHADAP PRODUKTIVITAS PEGAWAI NEGERI SIPIL DIBALAI PENGKAJIAN TEKNOLOGI PERTANIAN (BPTP) SULAWESI UTARA - Umboh, Brusli; Rorong, Arie; Londa, Verry (JURNAL ADMINISTRASI PUBLIK, 2015)
Abstract : Organizational culture is important when it comes to improving the performance of organizationsand personnel in it. Culture of the organization has a goal to change attitudes and behavior of existinghuman resources in order to increase labor productivity to face many challenges in the future. The purpose ofthis paper is to analyze the work culture and productivityThis research is descriptive-quantitative research. Quantitative research goal is to develop and usemathematical models, theories or hypotheses pertaining to natural phenomena. The population in this studywere employees who worked in the Institute for Agricultural Technology North Sulawesi with the number ofemployees as many as 97 employees.Results of this study show the influence of culture on the productivity of employees working for R2 = 0302, or30.2%. The statistics show that the variable work culture has a positive impact on the productivity ofemployees at the Institute for Agricultural Technology (BPTP) of North Sulawesi, which means that laborproductivity increased by 30.2% determined by or influenced by the culture of work, while the rest of 69, 8%are determined or influenced by other variables not examined in this studyKeywords: Organizational Culture, Productivity